PELAKSANAAN STRATEGI DIFFERENSIASI SEBAGAI SUATU STRATEGI BERSAING GUNA MEMPERTAHANKAN PELANGGAN ( Kasus Industri Jasa Pengiriman PT Indah Logistik Cabang Pekanbaru ) - Mulia, Rita; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In the higher levels of competition, companies must be able to deal withcompetitors that offer similar products. Implementation required the rightcompetitive strategy to win the competition. The implementation of the differentiationstrategy is the implementation of the policy by the company by providing a series ofimportant and valuable differences, in order to differentiate the products offered bythe company with competitors' products. This strategy is implemented by thecompany because consumers now have more choices in selecting a product. For thatthe company should be able to create a different product or service., Superior, andattractive than other companies in order to attract the attention of consumers.This study aims to identify and analyze the implementation of thedifferentiation strategy as an alternative strategy to retain customers and what arethe factors inhibiting PT Indah Logistic faced in implementing the differentiationstrategy. This is a descriptive study. The sampling technique used is AcidentalSampling data collected with interviews and observations.The results of this study indicate that the implementation of the differentiationstrategy undertaken by PT. Indah branch Logistic Pekanbaru pretty good. The besteffects are the product differentiation and image. Implementation Strategy andPersonnel Service differentiation is still pretty good company or not fullyimplemented by the company.Keywords: Implementation of Differentiation Strategy, Products, Services, Personnel, andImage